KRITIK SOSIAL DALAM NOVEL NAYLA KARYA DJENAR MAESA AYU - Sriwahyuni, Indah; Asri, Yasnur (Universitas Negeri Padang, 2020)
ABSTRACTThe aim of the study was to reveal the social criticism depicted in Djenar's Novel Nayla's works. This research is a qualitative descriptive research that is research by solving a problem that exists in the object. This study used a Socioligi approach to literary sociology theory. The data source in this study was Nayla's novel by Djenar Maesa Ayu. The research data is in the form of words and display of narrator sentences and story figures and story actions. Data collection is done by reading, understanding and analyzing the novel. The data analysis is done by interpreting the data with the theory used in the research. The data validation technique in this study has discussions with lecturers to obtain correct and true information. The results of this study were the social criticism of poverty, social criticism of crime, social criticism of family disorganization, social homosexual criticism, and social and environmental unrest. The conclusion of the results and the discussion that, the research is more to the social problems found in the novel.Â Kata kunci: kritik sosial, novel Nayla, Djenar Maesa Ayu.